Efektivitas Media Papan Edukasi Pintar Terhadap Kemampuan Literasi Dan Numerasi Pelajaran Matematika Kelas 1 SDN 02 Guyangan - Muhammad Rozikul Afnani; Atik Eva Nur Rizki; Wulan Sutriyani (LPPM Politeknik Pratama, 2023)
Considering that the culture of literacy in Indonesia is still low, has not taken root and has not taken root among humans. It's no secret that during the rise of popular culture, books are no longer a priority. This study aims to determine the effectiveness of smart education board media on literacy and numeracy abilities of grade 1 students at SDN 02 Guyangan in Mathematics subject matter Place Value of Numbers. This type of research is a quantitative experimental research, with a One-Group Pretest-Posttest Design. The research conducted in class 1 at SD N 2 Guyangan found that the use of the Smart Education Board media was effective in improving the literacy and numeracy skills of grade 1 students in the Place Value of Numbers material.